Numerical simulation of interfacial closures for 3D bubble column flows - Masood, Rao Muhammad Atif; Jovicic, Vojislav; Delgado, Antonio (Chemical Engineering & Technology, 2015)
Numerical investigation of flow hydrodynamics in a square cross-sectioned bubble column was conducted in a transient Euler-Euler environment by applying the simulation tool Ansys CFX 14.0. The influence of the drag coefficient (CD) was investigated and the results were also compared with drag force models. Furthermore, three different lift force models and a defined lift coefficient were studied. All results were compared with the available experimental data. All simulations were carried out for a single-hole sparger with given aspect ratio (H/D) and superficial gas velocity. Developing and improving computational fluid dynamics (CFD) tools for modeling of bubble column flows is of increasing interest. Numerical investigations of gas-liquid flow hydrodynamics in 3D square bubble columns were performed by means of a commercial CFD tool. The effect of the drag coefficient was determined and results were also compared to drag force models.
UnivIS-Import:2015-07-08:Pub.2015.tech.ITC.stmmec.numeri
Keywords: Bubble column; Computational fluid dynamics; Flow hydrodynamics; Interfacial closures; Numerical simulation